HARDWARE IMPLEMENTATION OF A MINIMALLY COMPLEX RFID BASED DATA RETRIEVAL SYSTEM - JAMALUL KARIB, NUR BAITI (Universiti Teknologi Petronas, 2008)
The topic of this project is 'Hardware Implementation of a Minimally Complex RFID Based Data Retrieval System'. Data retrieving has now become a need in our daily life. The focus of this project is on designing the data retrieval system and hardware implementation of the designed system. This project is then proceed to the stage of testing the data retrieval system that has been implemented. In this project, the circuit is designed to be built by using digital circuits. The circuit is divided into small parts according to their functions such as the update control logic, search control logic, reset control logic and the memory. Data retrieval system has a very wide range of applications. The data retrieval system in the library is used as the example of data retrieval system application in designing the system for this project. In this project, the data retrieval system builds to take the input from the RFID reader. RFID stands for Radio Frequency Identification. It is a technology that is using electromagnetic signals. RFID has a wide range of applications such as in a security system, items storage systems in factories and hypermarkets, books storage system in the libraries and many more. RFID has a lot of advantages as compared to the barcodes systems.